SURVIVAL OF SOME BACTERIAL SPECIES NO METAL AND CARTON SURFACES STORED AT ROOM TEMPERATURE FOR DIFFERENT PERIODS OF TIME. - M. AL-Shawi. , A. (The Iraqi Journal of Veterinary Medicine, 1994)
A total of 14 different bacterial species were monitored for their capabilities in survival on each of metal (coins) and carton surfaces. Species used were: B. subtilis, Br. abortus, Coryn. pyogenes, E. coli K1. pneumoniae, L. monocytogenes, Past. multocida, multocida, Pr. vulgaris, Ps. aeruginosa, Sal. typhi, Staph. aureus, Staph. epidermidis, Strept. equi and strept. zooepidemicus. Results showed that all species were recovered from carton surfaces after 7 days of storage at room temperature (18-24 °c), and only B. subtilis was detected from the same surface after 14 days of storage at the same temperature. But from metal surfaces only Staph. epidermidis was recovered after 7 days of storage.